Volume 7A: Structures and Dynamics 2015
DOI: 10.1115/gt2015-42461
|View full text |Cite
|
Sign up to set email alerts
|

Volume of Fluid (VOF) Analysis of Oil-Jet Lubrication for High-Speed Spur Gears Using an Adaptive Meshing Approach

Abstract: In high speed gearbox systems, the lubrication is generally provided using nozzles to create small oil jets that feed oil into the meshing zone. It is essential that the gear teeth are properly lubricated and that enough oil gets into the tooth spaces to permit sufficient cooling and prevent gearbox failure. A good understanding of the oil behaviour inside the gearbox is therefore desirable, to minimize lubrication losses and reduce the oil volume involved, and ensure gearbox reliability. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…5c, the generated oil film is spreading on the flank and parts of the oil are flung off directly during the impact process, which is then further supported by the acting centrifugal forces. The predicted results agree well with the work by Fondelli et al (1,12) and Keller et al (2,13) The illustration of the observable flow phenomenology during the OGI in Fig. 5 shows the complex structure of the prevailing two-phase flow -in its geometric shape and in its temporal evolution.…”
Section: Flow Phenomenologysupporting
confidence: 89%
See 3 more Smart Citations
“…5c, the generated oil film is spreading on the flank and parts of the oil are flung off directly during the impact process, which is then further supported by the acting centrifugal forces. The predicted results agree well with the work by Fondelli et al (1,12) and Keller et al (2,13) The illustration of the observable flow phenomenology during the OGI in Fig. 5 shows the complex structure of the prevailing two-phase flow -in its geometric shape and in its temporal evolution.…”
Section: Flow Phenomenologysupporting
confidence: 89%
“…Here and in the following discussions, the third impact of the oil-jet on the dry gear at is analysed. As concluded by Fondelli et al (12) , it was found that the preceding impacts contain start-up effects while subsequent impacts yield repetitive results.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Many industrial applications use impinging liquid jet to provide an effective mode of heat transfer, such as electrical motor [1], gearbox [2] and steel rolling [3]. For high-speed transmission systems, such as aircraft engines, turbomachinery, and drive trains, oil-jet is applied to the ball bearing cooling [4].…”
Section: Introductionmentioning
confidence: 99%